The changing epidemiology of dog bite injuries in the United States, 2005-2018 - Peter S. Tuckel; William Milczarski (BMC, 2020)
Abstract Background In 2018, the most recent year for which data are available, dog bites ranked as the 13th leading cause of nonfatal emergency department visits in the United States. As dog ownership spirals upwards in the United States, it is important to continue to monitor the epidemiology of dog bite injuries. This study provides contemporary data on the incidence of dog bites injuries in the United States and in New York and profiles individuals who have been treated for dog bites in emergency departments. The study also examines the demographic correlates of the rate of injuries at the neighborhood level in New York City and maps the rate in each neighborhood. Methods At the national level, the study examines longitudinal data on dog bite injuries from 2005 to 2018 gathered by the Centers for Disease Control and Prevention. For New York, the study analyzes data for 2005-2018 collected by the New York State Department of Health. A negative binomial regression analysis was performed on the state data to measure the simultaneous effects of demographic variables on the incidence of dog-related injuries. A thematically shaded map of the rate of dog bite injuries in New York City's neighborhoods was created to identify neighborhoods with higher-than-average concentration of injuries. Results In both the United States and New York the rate of dog-bite injuries increased from 2005 to 2011 and then underwent a significant decline. Injuries due to dog bites, however, still remain a sizable public health problem. Injuries are more prevalent among school-age children, inhabitants of less-densely populated areas, and residents of poorer neighborhoods. In New York City, poorer neighborhoods are also associated with fewer dogs being spayed or neutered. Conclusions To reduce the rate of dog bite injuries, prevention programs - particularly those which center on teaching the dangers of canine interactions with humans - should be targeted at children. Dog bite injuries tend to be clustered in identifiable neighborhoods. Dog bite prevention programs and stricter enforcement of dog laws can target these neighborhoods.